Patients right to privacy during medical services - Wroński, Konrad (Contemporary Oncology/Współczesna Onkologia, 2008)
The doctor providing medical services should pay special attention to patients’ privacy. For every patient privacy is a very sensitive, confidential and individual aspect of life. The following article presents legal aspects of patients’ right to privacy during hospital stay.